Epicenter of Knowledge; A Historic Exploration of Bayt Al Hikmah’s Significance - Mahmood, Anum (Journal of Research in Humanities, 2022)
The paper examines the library of the Muslim world, ‘House of Wisdom’, known to the world as ‘Bayt Al Hikmah’. The archive was made accessible to the public, where books were translated into Arabic so that the locals could get advantages from it. Not only the books from around the world were interpreted and translated in this library but original books were also produced. The Golden Age of the Muslim period was thus called golden since they acknowledged the importance of knowledge. The subsequent research paper discusses themes, historians and patrons, and workings of the House of Wisdom. On a historical basis, this research gathers and formulates pertinent evidence and resources about Bayt Al-Hikmah and its connected features. Thus a period of political and economic stability came into being, during the Abbasid rule where Baghdad became the pivot of knowledge and understanding. The impact Bayt Al-Hikmah left on the libraries was unprecedented